Dada : La fonction de refus - Waldberg, Patrick (Paris : Editions de la Différence, 1999)
Arp, Hans (Jean) ; Ball, Hugo ; Bloy, Léon ; Cazals, F.A. ; Charchoune, Serge ; van Doesburg, Theo ; Duchamp, Marcel ; Eggeling, Wiking ; Eissner, Xavier ; Ernst, Max ; Fauchery, Antoine ; Gauguin, Paul ; Grosz, George ; Hausmann, Raoul ; Höch, Hannah ; Janco, Marcel ; Lissitzky, El ; Man Ray ; Nadar ; Picabia, Francis ; Richter, Hans ; Schwitters, Kurt ; Serner, Walter ; Tzara, Tristan ; Vaché, Jacques ; Verlaine, Paul
Frans
boek